Global learning: innovative educational practice - Edward, Oswald Timothy; Idris, Siti Hafsyah; Munchar, Julina (Penerbit UiTM (UiTM Press), 2026)
Access to study abroad in higher education is still limited to students from affluent backgrounds or with outstanding academic results. To make this experience more inclusive for many, internationalisation in higher education has shifted its paradigm in the last few decades from the conventional demarcation of student mobility abroad to internationalisation at home (IaH) and internationalisation of the curriculum (IaC). Global learning is a high-impact educational practice that provides students with unique, authentic learning experiences beyond the classroom. This innovative teaching approach brings about a paradigm shift in classroom delivery and helps students explore different worldviews, cultures, and life experiences, globally and boundlessly. Global learning fosters intercontinental awareness and appreciation of diversity. In this session, students will gain extensive knowledge and understanding from experts and industry players overseas about the topics they learn in class.